Permainan Tradisional Estafet Tepung untuk Mengembangkan Sosial Emosional Anak Usia Dini - Mahmudatunnisa, Ismi; Kurniawati, Henie; Liharsari, Alini; Herawati, Ega (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Problems of social-emotional development of children who experience social limitations. These limitations occur due to several factors. For example, children prefer to play with handPhond than with peers. This can be overcome with the existence of traditional games that are useful for children's growth and development, mentally strong both physically and psychosocial-emotional. Traditional games that provide many benefits are traditional flour relay games where children will be happy when doing the game. The traditional game of flour relay leads to the social and emotional development of children because it involves many people. The purpose of this study is to solve the problem of how the traditional game of the flour relay develops early childhood social-emotional. This study uses a qualitative research method, namely taking data in the game book, which is developed with content analysis, namely by analyzing documents. The results of these games include children being able to have social-emotional intelligence, children have a sense of responsibility, and children have confidence (have a high leadership spirit since childhood) and can handle problems by deliberating (developing problem solving skills).